2021
DOI: 10.1021/acsomega.1c03862
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxymethylfurfural Enhances the Antiviral Immune Response in Macrophages through the Modulation of RIG-I-Mediated Interferon Production and the JAK/STAT Signaling Pathway

Abstract: 5-Hydroxymethylfurfural (5-HMF) exists in a wide range of sugar-rich foods and traditional Chinese medicines. The role of 5-HMF in antiviral innate immunity and its mechanism have not been reported previously. In this study, we reveal for the first time that 5-HMF upregulates the production of retinoic acid-inducible gene I (RIG-I)-mediated type I interferon (IFN) as a response to viral infection. IFN-β and IFN-stimulated chemokine gene expressions induced by the vesicular stomatitis virus (VSV) are upregulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…It also enhanced innate antiviral immunity in mice, resulting in elevated serum IFN‐β levels and decreased morbidity and viral load after infection with vesicular stomatitis virus (VSV). It has also been shown that 5‐HMF establishes a novel immunomodulatory mechanism against viral infections by enhancing IFN‐JAK/STAT signaling and increasing the production of type I interferon (IFN) through retinoic acid‐inducible gene I (RIG‐I) 23 . PCA, a natural phenolic acid, has many beneficial properties, including antioxidant, anti‐inflammatory, neuroprotective, antibacterial, antiviral, anticancer, anti‐osteoporosis, analgesic, antiaging, metabolism regulation, hepatoprotective, and protective effects on the renal, digestive and reproductive systems 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also enhanced innate antiviral immunity in mice, resulting in elevated serum IFN‐β levels and decreased morbidity and viral load after infection with vesicular stomatitis virus (VSV). It has also been shown that 5‐HMF establishes a novel immunomodulatory mechanism against viral infections by enhancing IFN‐JAK/STAT signaling and increasing the production of type I interferon (IFN) through retinoic acid‐inducible gene I (RIG‐I) 23 . PCA, a natural phenolic acid, has many beneficial properties, including antioxidant, anti‐inflammatory, neuroprotective, antibacterial, antiviral, anticancer, anti‐osteoporosis, analgesic, antiaging, metabolism regulation, hepatoprotective, and protective effects on the renal, digestive and reproductive systems 24 .…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that 5‐HMF establishes a novel immunomodulatory mechanism against viral infections by enhancing IFN‐JAK/STAT signaling and increasing the production of type I interferon (IFN) through retinoic acid‐inducible gene I (RIG‐I). 23 PCA, a natural phenolic acid, has many beneficial properties, including antioxidant, anti‐inflammatory, neuroprotective, antibacterial, antiviral, anticancer, anti‐osteoporosis, analgesic, antiaging, metabolism regulation, hepatoprotective, and protective effects on the renal, digestive and reproductive systems. 24 PCA administration to H1N1‐infected mice prevented weight loss and mortality and reduced lung index, viral titer, immune cell infectivity, and cytokine levels.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is crucial to identify novel anti-inflammatory compounds for the prevention and treatment of inflammation-relevant lung injury. 5-HMF is an active compound commonly found in sugar-rich heat-processed foods, including honey, coffee, dried fruit and fruit juices ( Shapla et al, 2018 ; Zou et al, 2021 ). Studies show that 5-HMF exerts anti-inflammatory or anti-allergic effects ( Zhao et al, 2013 ; Alizadeh et al, 2017 ), and can inhibit ROS production and the expression of inflammatory factors such as PGE2, IL-1β, IL-6 and TNF-α in LPS-stimulated RAW264.7 macrophages ( Zhao et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…This interaction initiates the assembly of complexes between TBK1 and OPTN, leading to transautophosphorylation and activation of TBK1 [83]. Subsequently, TBK1 phosphorylates interferon regulatory factor 3 (IRF3) [85], a key step in promoting type I IFN production and triggering an effective antiviral response [86].…”
Section: Golgi Apparatus and Tlr/rlr Signalingmentioning
confidence: 99%